A mind at a time - Levine, Melvin D. (New York : Simon & Schuster, 2002)
Shows parents how to identify their children's strengths and weaknesses to determine their individual learning styles and help them succeed in school. Discusses eight fundamental systems of learning.
Includes bibliographical references (p. [337]-340), filmography (p. 341-342), and index.
Library Journal.
New York Times.
Adult
Keywords: Child development; Cognition in children; Individual differences in children; Learning disabilities; Learning; Child development; Child psychology; Learning disabilities; Learning